P82 Multi-centre cross-specialty recommendations for the investigation of suspected adult onset secondary haemophagocytic lymphohistiocytosis (HLH). (20th April 2020) - Mackenzie, Strachan; Low, Ryan; Brown, Michael; Sanchez, Emilie; Gilmour, Kimberly; Youngstein, Taryn; Tatersall, Rachel; Carpenter, Benjamin; Patel, Amit; Mcnamara, Christopher; Manson, Jessica
Abstract: Background: Secondary HLH (sHLH) in adults is a paradigm of a disorder with multiple challenges. It is rare and under-recognised, clinical features are non-specific and heterogeneous, it may present to a broad range of specialties and there is no single test which can unambiguously diagnose the condition. The investigation of such patients often occurs in a piecemeal fashion, which causes delays in establishing diagnosis leading to missed opportunities to start treatment early. Treatment protocols are extrapolated from mostly paediatric data from the primary, genetic form of HLH with insufficient clinical trials in adults to provide robust evidence-based management approaches. There is a resultant wide range in clinical practice and sHLH has a high mortality rate. Addressing these issues and improving knowledge about the disorder therefore requires cross-speciality, multi-centre working. Within the UK, these challenges have begun to be addressed over the past 24 months, resulting in the creation of local and regional HLH MDTs, the formation of a national network of interested specialists (HASC: the HLH across-specialty collaboration) as well as the creation of a national HLH registry as part of the UK Histiocytosis Registry (UKHR). Methods: The aim of this project was to create a national guideline for the diagnosis and investigation of adult patients with suspected sHLH in order to start to standardise practice across the UK. Over 30 clinicians from a broad range of specialties, from both paediatric and adult practice, were consulted. These included sub-specialist input from rheumatology, haematology, infectious diseases, virology, nephrology, intensive care and immunology with collaborations from 15 centres around the UK. The HASC meetings were used as a forum to collaborate and develop the guidance. Results: We created an investigation algorithm dividing tests for work-up into 3 sections: 1. Routine initial work 2. HLH-specific testing, comprehensive infection work-up, guidance on tissue biopsy 3. Identification and work-up of suspected adult cases of familial/genetic HLH (fHLH). The guidance also uses HASC multi-professional expertise to provide approaches to controversial areas including ferritin and sCD25 thresholds in adults, deep skin biopsies for suspected intravascular lymphoma and specific scenarios such as neurological presentations and CAR-T therapy. Clinicians from different specialties across the UK and specialist laboratories with an interest in HLH have been identified in order to make the HLH network more accessible. The aim is to have the guideline hosted by Histio UK, and freely available on their website. Conclusion: This guideline is based on cross-specialty consensus expert opinion with reference to published literature in order to develop best practice. The coordinated investigation of patients with sHLH is key to improving early diagnosis and treatment and is just one part of the collaborative multi-faceted approach that is required to improve overall outcomes for patients with sHLH. Disclosures: S. Mackenzie None. R. Low None. M. Brown None. E. Sanchez None. K. Gilmour None. T. Youngstein None. R. Tatersall None. B. Carpenter None. A. Patel None. C. Mcnamara None. J. Manson None.